SOFTWARE AS A TOOL OF KNOWLEDGE - Ladislav, RUDOLF (Trends in education, 2013)
The paper deals with the use of software in education due to new knowledge of connectivity of various processes. It is a modern method of using the software for gaining knowledge and verifying theories and relations. There are described two types of software. Students verify processes on lines of high voltage due to temperature changes or impact of pollution on insulators. In standard condition of laboratories there is no possibility to research such complicated processes. In case of suitable software which is assembled for concrete functions there is possible to know and verify the reality in laboratory conditions. Software as a tool of learning has a big application in practice and in education.
Keywords: software; high voltage; line; connectivity; relation; process; learning